SPR741, Double- or Triple-Combined With Erythromycin and Clarithromycin, Combats Drug-Resistant Klebsiella pneumoniae, Its Biofilms, and Persister Cells - She, Pengfei; Liu, Yaqian; Xu, Lanlan; Li, Yimin; Li, Zehao; Liu, Shasha; Hussain, Zubair; Wu, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Klebsiella pneumoniae has emerged as a major clinical and public health threat owing to the increasing prevalence of healthcare-associated infections caused by multidrug-resistant or extensively drug-resistant strains. However, increasing antibiotic resistance and the absence of clinically effective antimicrobial agents make combination therapy an urgent need. This study investigated the anti-microbial activity of SPR741, a polymyxin B derivative, in combination with macrolide antibiotics (erythromycin and clarithromycin), against extensively drug-resistant and pandrug-resistant K. pneumoniae. Monotherapy, double, and triple combination therapies were performed to identify the most effective treatment combination using in vitro checkerboard, time-killing kinetics. Furthermore, we evaluated the biofilm eradication and persister cell-killing activity of these combinations using laser confocal microscopy and colony forming unit counting. In addition, a neutropenic mouse thigh infection model was used to assess the therapeutic efficacy and toxicity of the triple antibiotic combination against pandrug-resistant K. pneumoniae in vivo. Our results suggested that SPR741 combined with macrolides exhibited strong synergistic antibacterial activity against extensively drug-resistant and pandrug-resistant K. pneumoniae. These antibiotic combinations could also effectively eradicate highly resistant bacterial biofilms and persister cells in vitro and demonstrate considerable efficacy and low toxicity in vivo. In summary, our findings indicated that SPR741, in combination with macrolide antibiotics (double or triple combination), has the potential to serve as a novel treatment option against drug-resistant K. pneumoniae -related infections.